2017
DOI: 10.1007/s00015-016-0254-z
|View full text |Cite
|
Sign up to set email alerts
|

Exploring diffusion and sorption processes at the Mont Terri rock laboratory (Switzerland): lessons learned from 20 years of field research

Abstract: Transport and retardation parameters of radionuclides, which are needed to perform a safety analysis for a deep geological repository for radioactive waste in a compacted claystone such as Opalinus Clay, must be based on a detailed understanding of the mobility of nuclides at different spatial scales (laboratory, field, geological unit). Thanks to steadily improving experimental designs, similar tracer compositions in different experiments and complementary small laboratory-scale diffusion tests, a unique and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 40 publications
1
10
0
Order By: Relevance
“…All this translated into initial bulk and EDL porosities in the rock equal to 0.0397 and 0.1103, respectively. Total porosity was fixed to 0.15, according to the findings in previous laboratory and field experiments. , …”
Section: Setup Dimensions and Model Parametersmentioning
confidence: 99%
See 1 more Smart Citation
“…All this translated into initial bulk and EDL porosities in the rock equal to 0.0397 and 0.1103, respectively. Total porosity was fixed to 0.15, according to the findings in previous laboratory and field experiments. , …”
Section: Setup Dimensions and Model Parametersmentioning
confidence: 99%
“…Several diffusion experiments had already been performed at Mont Terri (DI, FM-C, DI-A1, DI-B, DI-A2, DR). In those experiments, synthetic porewater at equilibrium with the rock and containing tracers was continuously circulated through a packed-off borehole interval and the decrease in tracer concentrations in the liquid phase was monitored. Subsequently, a volume of rock surrounding the borehole was overcored and the tracer profiles in the rock were analyzed.…”
Section: Introductionmentioning
confidence: 99%
“…Countries like Switzerland, France, and Belgium have selected clayey rock as a candidate for geological disposal repositories of high-level radioactive waste. They conducted significant research and development on clayey rock site screening and feature evaluation and built underground clayey rock laboratories (Van Marcke et al, 2010;Jacops et al, 2015;Bossart et al, 2017;Leupin et al, 2017;Wigger et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Van Loon et al (2005) studied the diffusion behavior of some key elements (e.g., tritiated water (HTO), Cl − , Na + ) in clayey rocks, e.g., Opalinus Clay, using the diffusion cell method and obtained many migration parameters. In another study, Leupin et al (2017) presented the research results of the Mont Terri Laboratory about material migration in Opalinus Clay in the last 20 years, which provided valuable data for the safety evaluation of underground laboratories and disposal repositories in Switzerland. Additionally, Jacops et al (2015;2017) studied the diffusion coefficients of dissolved gas and HTO in Boom clayey rocks by the diffusion cell method, providing a useful experimental basis for the construction of disposal repositories in Belgium.…”
Section: Introductionmentioning
confidence: 99%
“…The retardation of radionuclide migration has been demonstrated for claystones, like the Swiss Opalinus Clay, in many laboratories as well as in-situ experiments, usually applying constant and homogeneous (geochemical) experimental conditions [2][3][4][5]. However, for many radionuclides it has been shown that sorption and migration are affected by geochemistry and can deviate by one or more orders of magnitude [6][7][8].…”
Section: Introductionmentioning
confidence: 99%